SOSIALISASI TUMBUHAN CIPLUKAN (PHYSALIS ANGULATA L.) SEBAGAI OBAT TRADISIONAL - Murnihati Sarumaha; Darmawan Harefa; Adam Smith Bago; Amaano Fau; Wira Priatin Lahagu; Toni Lastavaerus Duha; Musafir Zirahu; Hartaniat Warisman Lase (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The socialization in this service aims to find out the identification of ciplukan, the use of the ciplukan plant (Physalis angulata L) in Hiliganowo Village, and to find out the community's response to the ciplukan plant as a medicinal plant. The method used in this service is data collection techniques through observation, interviews and documentation. Based on the results and findings of research that has been carried out, the identification of ciplukan is that ciplukan is a wild plant in the form of a bush or shrub. Having a height of 0.1-1 m, ciplukan also has an indistinct main stem with quite a lot of branches and forks and has a hollow stem, a single leaf with a stem, a single flower with an oval or elliptical stem, and has a round fruit with seeds. Many are small and green when unripe and yellowish when ripe. The use of the ciplukan plant (Physalis angulata L) as a traditional medicine in Hiliganowo Village is used as a medicine for heartburn and allergies (itching on the skin).